Catalisadores à base de Mo, CoMo e NiMo incorporados por impregnação ou in situ em γ-Al2O3, ZrO2 e γ-Al2O3-ZrO2 - avaliação na hidrodessulfurização do tiofeno - Baston, Eduardo Prado (Universidade Federal de São Carlos, 2011)
The preparation of Mo, CoMo or NiMo catalysts supported on -Al2O3, ZrO2 and - Al2O3-ZrO2 was studied. The zirconia contend added into alumina was 20 or 40 % wt.. The supports were synthesized via sol-gel and impregnation or direct addition in the synthesis mixture were used to incorporate the metals. The solids were characterized by thermogravimetric analysis (TG/DTG), X-ray diffraction (XRD), X-ray fluorescence (XRD), Zeta potential, N2 adsorption/desorption, hydrogen temperature programmed reduction (H2- TPR), ultraviolet visible diffuse reflectance spectroscopy (DRS-UVvis), transmission electron microscopy (TEM) and evaluated in the HDS of thiophene used as model molecule. The results showed that the synthesis via sol-gel allowed the formation of the above supports with high specific surface area, with zirconia being highly distributed in the alumina framework. The metal incorporation through impregnation or in situ led to catalysts with Mo, Co or Ni species highly dispersed. The activity data of the thiophene HDS on these catalysts indicated a promoter effect of the incorporation of about 20% of zirconia in the alumina that was simultaneous to the well known Co or Ni promoter character, this evidencing that the Mo activity is affected by the nature of the promoter metal and the textural and physico-chemical properties of the supports, which are strongly involved in the HDS mechanism. The main products of the thiophene HDS were butene-1, n-butane, trans-butene-2 and cis-butene-2, result that corroborates the high selective nature of the Mo based catalysts. Due to the close values of the specific reaction rate of the thiophene HDS on the studied catalysts, it can be concluded that the in situ preparation led to catalysts with very similar properties to those prepared by traditional impregnation. This result is highly attractive from a commercial point of view because it eliminates several steps in the catalysts preparation process, therefore, decreasing the preparation time and costs of labor and energy.
Keywords: Hidrodessulfurização; Catalisadores molibdênio; CoMo; NiMo; Alumina; Zircônia; Tiofeno; ENGENHARIAS::ENGENHARIA QUIMICA